معاشرے میں افواہ پھیلانے کے بارے شرعی نقطہ نظر؛ حکم اور سزا - Saira Taiba; Hafiz Rizwan Abdullah (Pakistan Journal of Islamic Research)
Honor is the most valuable asset of a human being. As it is damaged by anyone, it urges him to take any step. Sometimes a person is more concerned with its safety even than his life. A man has been very sensitive in case of his honor. If this sensitivity is not taken into account, then there would be anxiety and unrest in the society. That is why Islam has declared it as haraam to slander, accuse, slander someone, blame game, transferring rather transforming people's words and spreading rumors. And determined punishments for people who are pursuing to damage respect and dignity of people so that evil would not spread in society and people would be protected from dissatisfaction. Moreover this is the age of media. So in this age, due to the fastest communication means and modern instruments, it is so easy to spread the wordings and leaving their impact upon people is quite a normal thing. Electronic and print media expose many things that cause confusion and anxiety in the society. The great contemporary temptation is the endless series of false propaganda and rumors that need harsh confrontation. In this environment, we can fight against rumors if we follow Islamic teachings and use possible tactics.  And we can make them ineffective, rather through these resources, the true Islamic teachings can be conveyed. This research article underlines this point in the context of Islamic teachings in order to ensure the protection of the fundamental right of human dignity through the prevention of rumors.